Enhanced Plasmonic Biosensors of Hybrid Gold Nanoparticle-Graphene Oxide-Based Label-Free Immunoassay - Nan-Fu Chiu; Chi-Chu Chen; Cheng-Du Yang; Yu-Sheng Kao; Wei-Ren Wu (Nanoscale Research Letters, 2018)
Abstract In this study, we propose a modified gold nanoparticle-graphene oxide sheet (AuNP-GO) nanocomposite to detect two different interactions between proteins and hybrid nanocomposites for use in biomedical applications. GO sheets have high bioaffinity, which facilitates the attachment of biomolecules to carboxyl groups and has led to its use in the development of sensing mechanisms. When GO sheets are decorated with AuNPs, they introduce localized surface plasmon resonance (LSPR) in the resonance energy transfer of spectral changes. Our results suggest a promising future for AuNP-GO-based label-free immunoassays to detect disease biomarkers and rapidly diagnose infectious diseases. The results showed the detection of antiBSA in 10 ng/ml of hCG non-specific interfering protein with dynamic responses ranging from 1.45 nM to 145 fM, and a LOD of 145 fM. Considering the wide range of potential applications of GO sheets as a host material for a variety of nanoparticles, the approach developed here may be beneficial for the future integration of nanoparticles with GO nanosheets for blood sensing. The excellent anti-interference characteristics allow for the use of the biosensor in clinical analysis and point-of-care testing (POCT) diagnostics of rapid immunoassay products, and it may also be a potential tool for the measurement of biomarkers in human serum.